EXPORT DEMAND FOR INDONESIA'S CRUDE PALM OIL (CPO) TO PAKISTAN: APPLICATION OF ERROR CORRECTION MODEL - Lisbeth Girsang; Ketut Sukiyono; Putri Suci Asriani (Badan Penerbitan Fakultas Pertanian (BPFP), 2018)
Crude Palm Oil is one of the agricultural export commodities which become a contributor of foreign exchange which is exported to Pakistan continuously but fluctuated from the year 1973 to 2016. The purpose of this study consisted of two things; the first is to identify the factors that influence the demand for Indonesia's CPO exports to Pakistan. The second is to analyze the relationship between the production of CPO, the international and domestic price of CPO, and the exchange rate of Rupiah toward the volume of Indonesian CPO exports to Pakistan both in the long and in the short term of time. This study used time series data (1973-2016). The analytical method used in this study was Error correction model (ECM) to examine the correlation of variables: Indonesian CPO production, the international and domestic price of CPO, the international price of coconut oil, the international price of soybean oil, Pakistan’s GDP per capita, the inflation in Pakistan, and the exchange rate of Rupiah toward the export variable of Indonesian CPO to Pakistan by using software E-Views 6.0. Based on the results of this study, it is concluded that the factor affecting the short-term demand of Indonesia's CPO exports to Pakistan is the international price of CPO which has a significant negative correlation, while the factor affecting long-term demand is the exchange rate of Rupiah toward the US which has a significant positive correlation. There is no correlation between both Indonesian CPO production and domestic price of CPO toward Indonesia's CPO exports to Pakistan both in the short and in the long term.